Identification and Adoption of Themes in The Big Bang Theory Sitcom to Foster Academic Cultural Competencies of Doctoral Students in English for Academic Conversation Classroom - Lasekan, Olusiji (Frontiers in Psychology, 2021)
The primary purpose of this study is to identify academic cultural themes in the popular television sitcom The Big Bang Theory (TBBT) in order to enhance doctoral students' awareness and acquisition of PhD competencies through formalized and explicit instruction. The secondary aim is to assess the impact of the selected academic themes on doctoral students’ acquisition of PhD competencies in an English for Academic Conversation classroom. Drawing upon the concept of thematic learning instruction, a qualitative research method involving six clusters of PhD competency reference framework developed by Durette et al. (2016) was adopted to identify the academic cultural themes depicted by the sitcom's main characters. This is followed by evaluating the effectiveness of an English for Academic Conversation course in fostering learners’ PhD competencies using selected identified academic cultural themes. The result showed that the sitcom's main characters demonstrate the personal and professional skills commonly possessed by a competent academic as an individual or group. This is evidenced as all the thirty-four identified skills traverse the six clusters of PhD competencies devised by Durette et al. (2016). Also, the impact assessment results revealed that the course fostered learners’ PhD competencies as they shared knowledge, past experience, and action plans of every selected academic theme. This work contributes to existing knowledge of doctoral competencies vital to promoting competency-based PhD programs in higher education.